Investigating the effects of nest shading on the green turtle (Chelonia mydas) hatchling phenotype in the Ogasawara islands using a field‐based split clutch experiment. Issue 9 (7th September 2020) - Kobayashi, Shohei; Endo, Daisuke; Kondo, Satomi; Kitayama, Chiyo; Ogawa, Ryuta; Arai, Katsuhiko; Watanabe, Gen; Kawaguchi, Maiko
Abstract: The Ogasawara Islands are an important rookery for the green turtle ( Chelonia mydas ) in the North Pacific. Green turtles possess temperature‐dependent sex determination, and warmer incubation temperatures produce more females than males. Therefore, conservation practices such as nest shading may be required for this population to mitigate the effect of global warming on their sex ratio. To consider the application of such conservation practices in the Ogasawara population, it is fundamental to understand how artificially modified nest environments will affect green turtle hatchling phenotypes that influence their fitness. Here, we investigated the effects of nest shading on green turtle hatchling phenotypes in the Ogasawara population by using a split clutch experiment equally separating the clutch, relocating each half‐clutch into an outdoor hatchery area either with or without shading, and observing the subsequent hatchling phenotype. Our results showed that the shading treatment produced hatchlings with a better self‐righting response and a larger carapace size. Additionally, the shading treatment mostly reduced the production of hatchlings with a nonmodal scute pattern and produced hatchlings with a smaller unabsorbed yolk sac, which may be associated with their residual yolk mass. These results suggest that conservation practices such as shading could alter not only the sex ratio but also the hatchling phenotype that influences their fitness. Hence, our results suggest that applications of such conservation strategies must be carefully considered. Abstract : Shading treatment affected the hatchling phenotype that influences the fitness of green turtle hatchlings in the Ogasawara population. Highlights: Nest shading affected the phenotype of green turtle hatchlings in the Ogasawara population. Conservation practices to mitigate the effects of global warming will alter the hatchling phenotype that influences hatchling fitness.